Consumer Buying Interest in The Sale of Scallop Products - Sasongko, Dimas Bayu; Prayoto, Prayoto; Rahardjo, R. Sugeng; Surahmat, Djoko; Wartini, Sri; Azhar, Awwala Maulidya (LPPM Universitas Ekasakti, 2024)
This study aims to analyze consumer buying interest in scallop products produced by PT. ILM. The factors studied include product quality, product image, product price, and consumer confidence. The research method used is a qualitative descriptive method with a survey approach. Data was obtained through observation, interviews, and the distribution of questionnaires to consumers. The results of the study show that product quality, brand image, and price have a significant influence on consumer buying interest. Most consumers have a positive perception of PT. ILM, which is reflected in their high level of satisfaction and loyalty. Therefore, companies need to maintain